(untitled) (Revista de Ciências Agroveterinárias, 2018)
The study of monthly rainfall probabilities is of great importance due to the increasing occurrences of extreme events in different regions of Brazil. However, the rainfall distribution at the southwest region of Paraná State, Brazil, is still unknown. Thus, the aim of this work is to assess the probabilistic distribution of rainfall frequency at Dois Vizinhos, in the southwest of Paraná State, Brazil. A probabilistic analysis was performed using a historic 40-year rainfall dataset (1973-2012). The gamma, Weibull, normal log, and normal probability distributions were compared. The distribution adherence was performed through Akaike Information Criterion, and the R statistical software was used for estimation. The results showed that the gamma and Weibull distributions were most suitable for probabilistic fitting. Based on this, the average annual rainfall for Dois Vizinhos (PR) was found to be 2,010.6 mm. Moreover, we found that throughout the year, October has the highest rainfall occurrence probability, with an 86% rainfall probability of above 150 mm and 64% rainfall probability above 200 mm.